Extending the Serum Half-Life of G-CSF via Fusion with the Domain III of Human Serum Albumin. (15th September 2013) - Zhao, Shuqiang; Zhang, Yu; Tian, Hong; Chen, Xiaofei; Cai, Di; Yao, Wenbing; Gao, Xiangdong
Abstract : Protein fusion technology is one of the most commonly used methods to extend the half-life of therapeutic proteins. In this study, in order to prolong the half-life of Granulocyte colony stimulating factor (G-CSF), the domain III of human serum albumin (3DHSA) was genetically fused to the N-terminal of G-CSF. The 3DHSA-G-CSF fusion gene was cloned into p PICZ α A along with the open reading frame of the α -factor signal under the control of the AOX1 promoter. The recombinant expression vector was transformed into Pichia pastoris GS 115, and the recombinant strains were screened by SDS-PAGE. As expected, the 3DHSA-G-CSF showed high binding affinity with HSA antibody and G-CSF antibody, and the natural N-terminal of 3DHSA was detected by N-terminal sequencing. The bioactivity and pharmacokinetic studies of 3DHSA-G-CSF were respectively determined using neutropenia model mice and human G-CSF ELISA kit. The results demonstrated that 3DHSA-G-CSF has the ability to increase the peripheral white blood cell (WBC) counts of neutropenia model mice, and the half-life of 3DHSA-G-CSF is longer than that of native G-CSF. In conclusion, 3DHSA can be used to extend the half-life of G-CSF.